1997
DOI: 10.1074/jbc.272.50.31636
|View full text |Cite
|
Sign up to set email alerts
|

hsp110 Protects Heat-denatured Proteins and Confers Cellular Thermoresistance

Abstract: The 110-kDa heat shock protein (hsp110) has long been recognized as one of the primary heat shock proteins in mammalian cells. It belongs to a recently described protein family that is a significantly diverged subgroup of the hsp70 family and has been found in organisms as diverse as yeast and mammals. We describe here the first analysis of the ability of hsp110 to protect cellular and molecular targets from heat damage. It was observed that the overexpression in vivo of hsp110 conferred substantial heat resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
190
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(207 citation statements)
references
References 30 publications
11
190
0
Order By: Relevance
“…They appear to possess many of the secondary structural features of hsp70 and are peptide chain-binding proteins. Although little is known about the cellular functions of hsp110, deletion mutational studies have defined its basic domains and indicate that it has a peptide-binding domain generally analogous to that of hsp70, while it also exhibits major functional differences from those of hsp70 (15,18). Less is understood at the molecular level of grp170 structure and function; however, cellular studies have shown that it binds to Ig chain in the ER, may be the ATPase responsible for protein import into the ER, and actively binds peptides from TAP (i.e., the transporter associated with Ag processing; Refs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They appear to possess many of the secondary structural features of hsp70 and are peptide chain-binding proteins. Although little is known about the cellular functions of hsp110, deletion mutational studies have defined its basic domains and indicate that it has a peptide-binding domain generally analogous to that of hsp70, while it also exhibits major functional differences from those of hsp70 (15,18). Less is understood at the molecular level of grp170 structure and function; however, cellular studies have shown that it binds to Ig chain in the ER, may be the ATPase responsible for protein import into the ER, and actively binds peptides from TAP (i.e., the transporter associated with Ag processing; Refs.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of hsp110 in parallel with hsp70 in the cytoplasm and of grp170 in parallel with grp78 in the ER of (apparently) all eukaryotic cells argues for important differential functions for these distantly related protein families. Indeed, present data indicate important functional differences between these large and small stress protein groups; e.g., hsp110 appears to be significantly more efficient than hsp70 in binding peptide chain but does not bind to ATP agarose, as does hsp70 (15,18); grp170 binds peptide from TAP, whereas grp78 does not (19,20).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Like Hsp70s, Hsp110s exhibit ATPase activity [3,4]. Unlike Hsp70s, however, Hsp110s do not actively fold proteins, but rather act as holdases to maintain the solubility of denatured model protein substrates [3,[5][6][7]. Hsp110s also function as NEFs for Hsp70s [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…They also show chaperone activity of their own. Unlike Hsp70s, Hsp110s lack the hallmark activity to assist in protein folding; however, they exhibit high activity in preventing aggregation of denatured proteins for which they are even more efficient than Hsp70s (40,41). For this reason, Hsp110s are called "holdases" in comparison with "foldases" for Hsp70s.…”
mentioning
confidence: 99%